2022
DOI: 10.7759/cureus.30942
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Impairment in Cardiovascular Disease Patients Taking Statins Versus Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Inhibitors: A Systematic Review

Abstract: Cardiovascular diseases (CVDs) are prevalent medical conditions affecting millions of people worldwide and are associated with significant morbidity and mortality. The main precursor of CVDs and the related events, such as hypertension and heart failure, is hyperlipidemia, most commonly an increase in low-density lipoproteins. Lipid-lowering drugs are cardinal in the treatment of CVDs. American College of Cardiology and American Heart Association have issued guidelines for lipid-lowering therapy, and statins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Neurocognitive adverse events have been observed in the use of LDL‐C lowering HMG‐CoA reductase inhibitors, which has been recognized that lowering LDL‐C is a key incentive in neuronal cell dysfunction (Shahid et al, 2022; Yuet et al, 2021). The main objective of this review article is to describe the effect of different PCSK9 levels (PCSK9 gene mutations and PCSK9 inhibitors) on neurocognitive adverse events through population samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurocognitive adverse events have been observed in the use of LDL‐C lowering HMG‐CoA reductase inhibitors, which has been recognized that lowering LDL‐C is a key incentive in neuronal cell dysfunction (Shahid et al, 2022; Yuet et al, 2021). The main objective of this review article is to describe the effect of different PCSK9 levels (PCSK9 gene mutations and PCSK9 inhibitors) on neurocognitive adverse events through population samples.…”
Section: Discussionmentioning
confidence: 99%
“…An early study had showed that the overexpression of neural apoptosis‐regulated convertase 1 (NARC‐1) gene, PCSK9, enhanced the recruitment of undifferentiated neural telencephalic progenitor cells toward the neuronal lineage, thus PCSK9 inhibition may affect the development of neurological disorders from this perspective (Seidah et al, 2003). Glucose metabolism disorder, N‐methyl‐ D ‐aspartic acid receptor regulation, and genetic variation have also been reported as susceptibility risk factors leading to neurological dysfunction and allow PCSK9 inhibitors to enter the brain (Shahid et al, 2022).…”
Section: Mechanism Of Pcsk9 Inhibition On Cnsmentioning
confidence: 99%
“…No increased risk of serious adverse events, including neurocognitive effects, gastrointestinal hemorrhage, cataracts, new onset diabetes mellitus, or myalgias were found [47]. In addition, specific analyses of neurocognition [48][49][50][51][52], including studies [53,54] that performed serial assessment using a formal standardized tool [55], did not find any relationship between PCSK9i or achieved LDL-C and adverse neurocognitive function.…”
Section: Safety Of Psk9 Inhibition and Low Ldl-cmentioning
confidence: 99%